2019
DOI: 10.1101/665869
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A systematic comparison of chloroplast genome assembly tools

Abstract: Chloroplasts are photosynthetic organelles in plant cells and contain their own genomic information. That genome can be utilized in different scientific fields like phylogenetics or biotechnology. Thus, different assemblers have been developed specialized in chloroplast assemblies. Those assemblers often use the output of whole genome sequencing experiments as input. Such sequencing data usually contain the complete chloroplast genome information, even if the sequencing aims for the core genome. Different asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
41
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(44 citation statements)
references
References 65 publications
3
41
0
Order By: Relevance
“…Additionally, organelle genomes may produce flip-flop configurations or other assembly isomers mediated by repeats [25][26][27]; these outcomes are not addressed by any of the abovementioned pipelines/toolkits, except GetOrganelle. This capability also was not investigated by Freudenthal et al [24].…”
Section: Introductionmentioning
confidence: 88%
See 4 more Smart Citations
“…Additionally, organelle genomes may produce flip-flop configurations or other assembly isomers mediated by repeats [25][26][27]; these outcomes are not addressed by any of the abovementioned pipelines/toolkits, except GetOrganelle. This capability also was not investigated by Freudenthal et al [24].…”
Section: Introductionmentioning
confidence: 88%
“…Freudenthal et al [24] showed that GetOrganelle has moderate efficiency in both time and memory usage among tested assemblers. However, they only used the default options for evaluation, which are designed to have high chloroplast genome completion rate, rather than high computational efficiency.…”
Section: Computational Consumption Of Getorganellementioning
confidence: 99%
See 3 more Smart Citations